2005
DOI: 10.1002/cncr.20948
|View full text |Cite
|
Sign up to set email alerts
|

Therapy‐related changes in body size in Hispanic children with acute lymphoblastic leukemia

Abstract: BACKGROUND The objective of this study was to examine changes over time in body mass index (BMI) from diagnosis through chemotherapy for pediatric patients with B‐precursor acute lymphoblastic leukemia (ALL). METHODS The study cohort consisted of 141 white Hispanic pediatric patients who were diagnosed with ALL and were treated at 2 South Texas pediatric oncology centers between 1993 and 2002. Changes in age‐standardized and gender‐standardized BMI scores were assessed. RESULTS The study cohort exhibited a ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
3
13
0
1
Order By: Relevance
“…The risk of an increased BMI compared with population controls has been previously reported among survivors of childhood ALL,6–19 with most studies examining patients treated before 1990, when cranial radiotherapy combined with less intensive chemotherapy regimens were used more commonly. Cranial radiotherapy >20 Gy was a commonly identified risk factor for increased BMI among patients in these studies 8, 10, 12, 13.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The risk of an increased BMI compared with population controls has been previously reported among survivors of childhood ALL,6–19 with most studies examining patients treated before 1990, when cranial radiotherapy combined with less intensive chemotherapy regimens were used more commonly. Cranial radiotherapy >20 Gy was a commonly identified risk factor for increased BMI among patients in these studies 8, 10, 12, 13.…”
Section: Discussionmentioning
confidence: 94%
“…However, because these associations have been identified primarily among patients treated before 1990, they may not be applicable to more contemporary regimens that utilize less cranial radiotherapy but more intensive chemotherapy, including more potent corticosteroids 1. Studies that examined patients treated in the contemporary era have reported increased obesity even in the absence of radiotherapy,18, 19 but to our knowledge have not identified which elements of chemotherapy may be responsible, nor have they examined blood pressure changes.…”
mentioning
confidence: 95%
“…Adiposity in survivors of childhood leukemia (8,9,2327) and brain tumors (28, 29) has been studied. The prevalence of overweight and obesity, as measured by BMI, in childhood acute lymphoblastic leukemia survivors ranges between 21% and 54% (overweight) and 14% and 30% (obese) in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…For the ones overweight at diagnosis, BMI exhibited no consistent pattern of increase or decrease over time. For the obese sub cohort, there was described a slight overall decrease over time [10]. Gender-dependent differences in weight gain pattern have been already reported [11].…”
Section: Introductionmentioning
confidence: 95%